1995
DOI: 10.1002/pro.5560040705
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the spatial structure of eukaryotic ornithine decarboxylases

Abstract: We used sequence and structural comparisons to determine the fold for eukaryotic ornithine decarboxylase, which we found is related to alanine racemase. These enzymes have no detectable sequence identity with any protein of known structure, including three pyridoxal phosphate-utilizing enzymes. Our studies suggest that the N-terminal domain of ornithine decarboxylase folds into a fi/a-barrel. Through the analysis of known barrel structures we developed a topographic model of the pyridoxal phosphate-binding dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
287
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(290 citation statements)
references
References 47 publications
3
287
0
Order By: Relevance
“…CysM consists of two domains, reflecting the typical fold of type II PLP enzymes [22,33] with the cofactor pyridoxal-phosphate covalently bound to the invariant lysine residue (Lys 51 ) at the active site. The crystals described here are of the same space group as those used for the initial structure determination [16], but the crystallographic data collection was carried out without the addition of cryo-protectant, i.e.…”
Section: Cysm Shows Open and Closed Conformations In The Absence Of Smentioning
confidence: 99%
“…CysM consists of two domains, reflecting the typical fold of type II PLP enzymes [22,33] with the cofactor pyridoxal-phosphate covalently bound to the invariant lysine residue (Lys 51 ) at the active site. The crystals described here are of the same space group as those used for the initial structure determination [16], but the crystallographic data collection was carried out without the addition of cryo-protectant, i.e.…”
Section: Cysm Shows Open and Closed Conformations In The Absence Of Smentioning
confidence: 99%
“…Grishin et al have proposed a topographic model of the PALP-binding domain of eukaryotic and prokaryotic ODCs by the analysis of known barrel structures of ODCs. 25) They classified the PALP-utilizing enzymes into seven fold types from the predicted secondary structures, and showed that the prokaryotic ODCs, prokaryotic LDCs, and bacterial inducible ADCs belong to fold type I. One of these, inducible ODC from Lactobacillus 30a, has three amino acids involved in PALP binding in its active center.…”
Section: Amino Acid Sequence Homologies Of S Ruminantium Adc With Otmentioning
confidence: 99%
“…Both ALAS and AAT belong to the same predicted fold type group (i.e., fold type I) and the a subfamily of the PLP-dependent enzymes (Alexander et al, 1994, Grishin et al, 1995. The availability of AAT high-resolution crystal structures and the knowledge of functions of many of its active site residues enable sequence alignment with AAT to be an efficient tool to predict the function(s) of a specific amino acid residue in ALAS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Grishin et al (1995) classified all PLP-dependent enzymes with known sequences into sevenfold types (i.e.? fold I-VII) and placed ALAS in the same fold as that of AAT (i.e., fold I).…”
mentioning
confidence: 99%